Strategi Optimalisasi Perpustakaan Digital Berbasis Literasi Digital Di Madrasah Ibtidaiyah Baitussalam Cerme Gresik - Mega Arum Krismaya Zainudin; Mulyadi; Muhamad Arif (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2026)
This study aims to analyze the advantages, challenges, and optimization efforts of the digital library at MI Baitussalam, Dusun Betiring, Desa Banjarsari, Kecamatan Cerme. This research employed a qualitative descriptive method, with data collected through interviews, observations, and documentation. The results indicate that the digital library offers several advantages, including modern facilities, e-books, Smart TV, and internet access, which support interactive and flexible learning. However, its utilization faces several challenges, such as low student reading interest, limited number of computers, lack of innovative digital literacy programs, and occasionally unstable internet connection. Optimization efforts include reading literacy programs, the use of Smart TV, parental involvement, addition of computers, teacher training, and enrichment of digital collections. In conclusion, the digital library at MI Baitussalam has great potential to improve students' literacy, but its effectiveness requires collaborative support among the school, teachers, students, and parents, as well as sustainable innovative literacy programs.